ANALISIS KETERAMPILAN DASAR MENGAJAR MAHASISWA PRODI PENDIDIKAN MATEMATIKA SEBAGAI CALON GURU MATEMATIKA PADA MATA KULIAH PENGAJARAN MIKRO [ANALYSIS OF BASIC TEACHING SKILLS OF MATHEMATICS EDUCATION STUDY PROGRAM STUDENTS AS PROSPECTIVE MATHEMATICS TEACHERS IN MIKRO TEACHING COURSES] - Imelda, Imelda; Situngkir, Friska Ledina (Universitas Pelita Harapan, 2024)
Basic teaching skills are skills needed by prospective teachers to become effective, efficient and professional teachers. Mathematics Education Study Program students are prepared to become prospective teachers with good basic teaching skills in microteaching courses. Micro teaching requires students to be able to compile lesson plans in the form of lesson plans or teaching modules. Then the lesson plan is practiced in classroom learning. It is during this teaching practice that students demonstrate these basic teaching skills. In theory, students understand the basic skills of teaching. However, what about when practicing. This study aims to describe the basic teaching skills of Mathematics Education Study Program students as prospective Mathematics teachers. The research method is qualitative descriptive. The subjects in this study were 13 students of the Mathematics Education Study Program at Santo Thomas Catholic University, 6th semester students of the 2022/2023 academic year. Data were collected from observation, documentation and interviews. The results of the analysis of the basic teaching skills of prospective Mathematics teachers in the Mathematics Education Study Program include the skills of opening and closing lessons well (4.1), the skills of explaining are quite good (3.95), the skills of asking questions are quite good (3.64), the skills of giving reinforcement are good (4.61), the skills of holding variations are quite good (3.93), the skills of guiding group discussions are quite good (3.93), the skills of managing class and discipline are good (good), the skills of teaching small groups and individuals are quite good (3.7). Thus it can be concluded that there are still some basic teaching skills that need to be improved by students.BAHASA INDONESIA ABSTRACT: Keterampilan dasar mengajar adalah keterampilan yang diperlukan oleh calon guru untuk menjadi guru yang efektif, efisien dan professional. Mahasiswa Prodi Pendidikan Matematika dipersiapkan menjadi calon guru dengan keterampilan dasar mengajar yang baik dalam mata kuliah pengajaran Mikro. Pengajaran Mikro mengharuskan mahasiswa untuk mampu menyusun rencana pembelajaran baik berupa RPP ataupun modul ajar. Kemudian rencana pembelajaran tersebut dipraktekkan dalam pembelajaran di kelas. Pada saat praktek mengajar inilah mahasiswa menunjukkan keterampilan dasar mengajar tersebut. Secara teori mahasiswa memahami keterampilan dasar mengajar. Namun, bagaimana dengan saat prakteknya. Penelitian ini bertujuan untuk mendeskripsikan keterampilan dasar mengajar mahasiswa Prodi Pendidikan Matematika sebagai calon guru Matematika. Metode penelitian adalah kualitatif deskriptif. Subjek dalam penelitian ini berjumlah 13 mahasiswa prodi Pendidikan Matematika Universitas Katolik Santo Thomas mahasiswa semester 6 TA 2022/2023. Data dikumpulkan dari hasil observasi, dokumentasi dan wawancara. Hasil analisis keterampilan dasar mengajar calon guru Matematika Prodi Pendidikan Matematika antara lain keterampilan membuka dan menutup pelajaran baik (4,1), keterampilan menjelaskan cukup baik (3,95), keterampilan bertanya cukup baik (3,64), keterampilan memberi penguatan baik (4,61), keterampilan mengadakan variasi cukup baik (3,93), keterampilan membimbing diskusi kelompok cukup baik (3,93), keterampilan mengelola kelas dan disiplin baik (baik), keterampilan mengajar kelompok kecil dan perorangan cukup baik (3,7). Dengan demikian dapat disimpulkan bahwa masih ada beberapa keterampilan dasar mengajar yang perlu ditingkatkan oleh mahasiswa antara lain keterampilan menjelaskan, bertanya, keterampilan mengadakan variasi, membimbing diskusi kelompok dan keterampilan mengajar kelompok kecil dan perorangan.